Alpha-Lipoic Acid (ALA)-Related Insulin Autoimmune Syndrome - Shahrour, Hala; Alqedra, Mohamed; Almazrouei, Raya (Journal of Diabetes and Endocrine Practice, 2025)
Insulin autoimmune syndrome (IAS) is a rare cause of hypoglycemia characterized by autoantibodies against endogenous insulin, often triggered by sulfhydryl-containing compounds such as alpha-lipoic acid (ALA). We report the case of a 43-year-old previously healthy woman who presented with recurrent fasting and postprandial hypoglycemia. Biochemical evaluation revealed inappropriately elevated insulin and C-peptide levels with negative sulfonylurea screen and no pancreatic lesion on imaging. Further history uncovered recent use of ALA, and markedly elevated insulin autoantibodies confirmed the diagnosis of ALA-induced IAS. Discontinuation of the supplement and dietary modification led to complete resolution of symptoms. This case highlights the importance of considering IAS in the differential diagnosis of unexplained hypoglycemia and underscores the need for detailed medication and supplement history.
Keywords: insulin autoimmune syndrome; hypoglycemia; alpha-lipoic acid; insulin autoantibodies; drug-induced autoimmunity